Artificial Urinary Sphincter: Long-Term Results and Patient Satisfaction - Drogo K. Montague (Advances in Urology)
The published evidence concerning the safety, efficacy, and patient satisfaction for implantation of the current model of the artificial urinary sphincter (AS 800) in men with post prostatectomy urinary incontinence was the objective of this review. A Pub Med English language literature search from 1995 to 2011 was performed. A majority of men who undergo AUS implantation for post prostatectomy urinary incontinence achieve satisfactory results (0 to 1 pad per day). Infection rates range from 0.46 to 7%, cuff erosion rates range from 3.8 to 10%, and urethral atrophy ranges from 9.6 to 11.4%. Kaplan-Meier 5 year projections for freedom from any reoperation were 50% for a small series and 79.4% for a larger series. Kaplan-Meier projections for freedom from mechanical failure were 79% at 5 years and 72% at 10 years. In another series 10 year projections for freedom from mechanical failure were 64%. Although the artificial urinary sphincter (AUS) is the gold standard for the treatment of this disorder, most men will continue to need at least one pad per day for protection, and they are subject to a significant chance of future AUS revision or replacement.